iNutritionApp: mobile application for nutrition monitoring using FatSecret API / Nurul Nabilah Roslan ... [et al.] - Roslan, Nurul Nabilah; Jamaluddin, Muhammad Nabil Fikri; Ibrahim, Alif Faisal; Mohd Fauzi, Shukor Sanim; Razak, Tajul Rosli; JM Gining, Ray Adderley (UiTM Cawangan Perlis, 2021)
Mobile application is a software designed to run on smartphones, tablet computers, and other mobile devices. The growing millions of users who are using mobile applications have contributed to an increase in the development of the mobile applications for enterprises, education, the social network and healthcare. Widely used healthcare application nowadays includes general health and wellness, tele-medicine, personal coaching and consultation, medical record tracking, custom reminders and various health management apps. This paper presents a mobile application related to general health and wellness named as iNutritionApp for providing nutrient information, tracking nutrition and calorie intakes with the integration of FatSecret API. The API provides nutritional information based on type of food provided by user. The application was intended to overcome manual calorie intake calculations and assists diet plan. Development methodology of this mobile application utilizes three phases that are system requirements, system design and development, as well as testing. Technology acceptance model with three parts were conducted with 30 respondents by evaluating the developed mobile application through questionnaires. Results of the testing showed that perceived of usefulness (PU) part achieved highest mean score compared to perceived ease of use (PEOU) that include user interface design and navigation parts. Therefore, features and functionality offered by the iNutritionApp is proven to be useful for user in tracking calorie intakes and provide access to nutritional information.